PENGARUH KREDIBILITAS CELEBRITY ENDORSER JKT48 TERHADAP PURCHASE INTENTION DENGAN BRAND AWARENESS SEBAGAI VARIABEL MEDIASI PADA SEPEDA MOTOR HONDA BEAT DI KOTA MALANG - Stefani Untono (Ma Chung Press, 2016)
This research discusses the influence of credible celebrity endorser JKT48 to the Purchase Intention Honda Beat motorcycle in the city of Malang directly and indirectly through brand awareness as a mediating variable. The use of celebrity endorser in ads into one solution in improving the intention to buy the product and strategies to compete in attracting the attention of consumers. This research is a quantitative research, data collection was conducted using a survey method and collection of data using questionnaires with non probability sampling method on 100 respondents of a motorcycle’s consumers in the city of Malang. Furthermore, the data were processed using path analysis techniques. The results showed that the celebrity endorser's credibility variable and brand awareness variable has a positive and significant to influence purchase intentions motorcycle products Honda Beat. Then, the variable brand awareness be intervening variables also have a significant influence and mediate the influence of celebrity endorser's credibility against the intentions of purchasing motorcycle product Honda Beat.